If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(x + -2) = 3 + -1(2x + -4) Reorder the terms: 5x(-2 + x) = 3 + -1(2x + -4) (-2 * 5x + x * 5x) = 3 + -1(2x + -4) (-10x + 5x2) = 3 + -1(2x + -4) Reorder the terms: -10x + 5x2 = 3 + -1(-4 + 2x) -10x + 5x2 = 3 + (-4 * -1 + 2x * -1) -10x + 5x2 = 3 + (4 + -2x) Combine like terms: 3 + 4 = 7 -10x + 5x2 = 7 + -2x Solving -10x + 5x2 = 7 + -2x Solving for variable 'x'. Reorder the terms: -7 + -10x + 2x + 5x2 = 7 + -2x + -7 + 2x Combine like terms: -10x + 2x = -8x -7 + -8x + 5x2 = 7 + -2x + -7 + 2x Reorder the terms: -7 + -8x + 5x2 = 7 + -7 + -2x + 2x Combine like terms: 7 + -7 = 0 -7 + -8x + 5x2 = 0 + -2x + 2x -7 + -8x + 5x2 = -2x + 2x Combine like terms: -2x + 2x = 0 -7 + -8x + 5x2 = 0 Begin completing the square. Divide all terms by 5 the coefficient of the squared term: Divide each side by '5'. -1.4 + -1.6x + x2 = 0 Move the constant term to the right: Add '1.4' to each side of the equation. -1.4 + -1.6x + 1.4 + x2 = 0 + 1.4 Reorder the terms: -1.4 + 1.4 + -1.6x + x2 = 0 + 1.4 Combine like terms: -1.4 + 1.4 = 0.0 0.0 + -1.6x + x2 = 0 + 1.4 -1.6x + x2 = 0 + 1.4 Combine like terms: 0 + 1.4 = 1.4 -1.6x + x2 = 1.4 The x term is -1.6x. Take half its coefficient (-0.8). Square it (0.64) and add it to both sides. Add '0.64' to each side of the equation. -1.6x + 0.64 + x2 = 1.4 + 0.64 Reorder the terms: 0.64 + -1.6x + x2 = 1.4 + 0.64 Combine like terms: 1.4 + 0.64 = 2.04 0.64 + -1.6x + x2 = 2.04 Factor a perfect square on the left side: (x + -0.8)(x + -0.8) = 2.04 Calculate the square root of the right side: 1.428285686 Break this problem into two subproblems by setting (x + -0.8) equal to 1.428285686 and -1.428285686.Subproblem 1
x + -0.8 = 1.428285686 Simplifying x + -0.8 = 1.428285686 Reorder the terms: -0.8 + x = 1.428285686 Solving -0.8 + x = 1.428285686 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.8' to each side of the equation. -0.8 + 0.8 + x = 1.428285686 + 0.8 Combine like terms: -0.8 + 0.8 = 0.0 0.0 + x = 1.428285686 + 0.8 x = 1.428285686 + 0.8 Combine like terms: 1.428285686 + 0.8 = 2.228285686 x = 2.228285686 Simplifying x = 2.228285686Subproblem 2
x + -0.8 = -1.428285686 Simplifying x + -0.8 = -1.428285686 Reorder the terms: -0.8 + x = -1.428285686 Solving -0.8 + x = -1.428285686 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.8' to each side of the equation. -0.8 + 0.8 + x = -1.428285686 + 0.8 Combine like terms: -0.8 + 0.8 = 0.0 0.0 + x = -1.428285686 + 0.8 x = -1.428285686 + 0.8 Combine like terms: -1.428285686 + 0.8 = -0.628285686 x = -0.628285686 Simplifying x = -0.628285686Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.228285686, -0.628285686}
| -5(3x-2)+4(3x-1)-8(4x-5)= | | 8x-155=3x+10 | | 9-5x-7-10x=5 | | -17=8(r-3)+7(1+6r) | | -2(x+2)=-6x-4 | | 10+5q=11+4q | | 2x^4-22x^2-36x-16=0 | | 4z-11-z+5=0 | | 6b-8=16+10b | | (6x+1)=(22-x) | | X+2x+2x-4+3(2x-4)=61 | | 10b+16=6b-8 | | 6=-8(a-7)-7(1+5a) | | 3x-8=x+13 | | 4t-7=5(t+2) | | 3y-4=-20 | | 6x+-14=58 | | 40-3n= | | -39-10=8x+15 | | y/2-5y/6+1/3=12 | | 6x-3=3x+12 | | 8-.06k=8 | | t-1=-t+2 | | 17.83=3g+3.67 | | 2w-7+3w=5-4w+7 | | 51=4x+15 | | ax+bx+cx=0 | | 4d+9e+7d+8e= | | 2(8+8v)=144 | | 4(u-2)=3u+2-4(-4u-2) | | -13-4=14-7x | | 5(7b-2)=95 |